(untitled) (Research, Society and Development, 2021)
Sepsis is the presence of degeneration in some organs or systems at risk of organic dysfunction that may have fungal, viral, bacterial or protozoal origin. Thus, sepsis can evolve quickly when diagnosed late and in the absence of an adequate assessment, accounting for 80% of deaths in the Intensive Care Units (ICU). Furthermore, a multiprofessional team must aim at eliminating the infection, administering therapy and controlling organic functions. This is a systemic literature review whose objective is to describe the findings regarding control factors and the progression of sepsis in the Intensive Care Unit. Nevertheless, it was found that patients with sepsis may have psychomotor, pulmonary and renal dysfunctions. Thus, a multidisciplinary team is needed to carry out an early diagnosis of the disease. On the other hand, the blood count presents a main tool for identifying sepsis. It was evident that the appearance of complications is associated with the length of hospital stay, prolonged use of drugs and invasive devices. Nevertheless, in the epidemiological profile of patients, there is a prevalence of males, with pre-existing comorbidities, aged between 18 and 25 years and especially neonates who were born underweight, have a low amount of vitamin D3 or have a high-risk prenatal care. At the same time, the realization of a safe and quality prenatal care proved to be promising in the prevention of sepsis. In the meantime, it is important that the health professional is committed to the techniques and assistance provided.